1988
DOI: 10.1111/j.1476-5381.1988.tb11451.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative affinities of drugs acting at cholinoceptors in displacing agonist and antagonist radioligands: the NMS/Oxo‐M ratio as an index of efficacy at cortical muscarinic receptors

Abstract: 3 Full agonists such as carbachol and muscarine possessed a ratio ofpotencies against the antagonist versus the agonist ligand (NMS/Oxo-M ratio) of >4000. 4 Compounds which have been shown previously to display partial agonist activity in functional assays e.g. pilocarpine and RS86 had intermediate NMS/Oxo-M ratios of 100-150. A second group of compounds which included oxotremorine had somewhat higher ratios (500-1400). 5 The ratio of affinity constants for the two assays predicted the ability of agonists to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 23 publications
(17 reference statements)
4
71
0
Order By: Relevance
“…It is clear that THA is not an irreversible inhibitor of acetylcholinesterase, as the inhibition was not timedependent and was rapidly reversible by dilution. The results indicate that THA does not bind to the catalytic ('esteratic') site and it has been suggested by others (Steinberg et al, 1975) Freedman et al, 1988).…”
Section: Discussionsupporting
confidence: 48%
“…It is clear that THA is not an irreversible inhibitor of acetylcholinesterase, as the inhibition was not timedependent and was rapidly reversible by dilution. The results indicate that THA does not bind to the catalytic ('esteratic') site and it has been suggested by others (Steinberg et al, 1975) Freedman et al, 1988).…”
Section: Discussionsupporting
confidence: 48%
“…Thus full agonists such as carbachol and muscarine have relatively low potency compared with that seen in parotid gland, and partial agonists such as pilocarpine and RS-86 produce a smaller maximal response relative to carbachol (Fisher et al, 1983;Freedman, 1986;Freedman et al, 1988). To date the only compounds with sufficient efficacy to stimulate phosphatidyl-inositol turnover in cerebral cortex have been quaternary agonists such as carbachol, muscarine, oxotremorine-M and acetylcholine itself.…”
Section: Introductionmentioning
confidence: 99%
“…3 H]-Oxotremorine-M (muscarinic agonist) binding anity ratio and functional assessment of muscarinic drugs in rat cortex, which was presumed to be primarily of the M 1 receptor sub-type was, therefore, of interest (Freedman et al, 1988). These studies resulted in the development of a simple radioligand binding assay, the results of which could estimate the relative intrinsic activity of muscarinic compounds at M 1 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Ligands which bind with higher anity to the inactive state of the receptor have been demonstrated to be inverse agonists (Sammama et al, 1993;Le, 1995). These dierent agonist states have been shown to exist for several receptors such as serotonin, dopamine, muscarinic and badrenoreceptors (Clawges et al, 1997;Freedman et al, 1988;Garnier et al, 1998;Houston & Howlett, 1998;Lahti et al, 1992;Tayebati et al, 1999). It has previously been reported that the ratio of the anity of a compound for high and low agonist anity states of muscarinic receptors is a reasonable prediction of intrinsic activity (Freedman et al, 1988;Loudon et al, 1997;Tayebati et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation